FULFILLMENT OF THE RIGHTS AND LEGAL REMEDIES OF FOREIGN WORKERS WITH CONTRACT STATUS WHICH ARE CARRIED OUT OF TERMINATION OF EMPLOYMENT JUSTICE PERSPECTIVE - Selamat, Selamat; Septyanun, Nurjannnah; Erwin, Yulias (Jurnal Ilmiah Advokasi, 2025)
Foreign workers in Indonesia have skills in the transfer of knowledge or know-how. In practice, foreign workers often have problems, such as layoff disputes. This research is a normative research, with a Law approach and a Case Approach. The legal materials used are primary, secondary, and tertiary, along with the literature data collection. Data analysis is descriptive and analytical with a qualitative approach. The research results are, first, that the legal protection of the rights of foreign workers who are unilaterally laid off has been regulated in Article 62 and Article 156 of Law Number 13 of 2003 concerning Manpower and strengthened by Government Regulation Number 35 of 2021. The rights obtained by the laid-off TKA are in the form of Severance Pay, Service Period Award Money, and Rights Replacement Money. However, not all of these rights can be obtained. Second, legal remedies can be taken by workers who are laid off due to the employer's failure to fulfil their rights through litigation and non-litigation settlement efforts and in the case of TKA, based on decision Number 12/Pdt.Sus-PHI/2021/PNMtr, the rights of TKA granted by the judge are basic salary from March to September 2020, with a calculation: Rp.21,750,00.00 x 7 = Rp. 152,000,000.00. It was not granted regarding severance pay based on legal reasoning; the judge's decision still referred to the positivistic legal aspect. Keywords : Employment Rights; Foreign-Employment Force; Court-Industrial-Relations Decisions